Pro Novell Open Enterprise Server - Vugt, Sander van (Apress, 2012)
This book is about Novell Open Enterprise Server. With Open Enterprise Server, Novell launched a new generation of server operating system, following a 20-year long tradition with NetWare. Open Enterprise Server is unique in the industry due to its two versions: one for Linux and another for NetWare. This book is meant as a guide to Open Enterprise Server, familiarizing administrators with this new server platform and helping them integrate it into their network system. This book covers both versions of Open Enterprise Server, helping readers integrate both versions of Open Enterprise Server, along with Windows and Linux PCs, into their network.ord,